A Decade-long Comparison of Prestroke Health Behaviors Among Hypertensive Stroke Patients in Mainland China. Issue 1 (February 2022) - Liu, Qun-Hong; Tan, Ju-Xiang; Hu, Cai-Xia; Hu, Dan-Lu; Wan, Li-Hong
Abstract : ABSTRACT: BACKGROUND: Patients with hypertension are at a high risk for stroke, but a healthy lifestyle can greatly reduce the risk of stroke. However, there has been no research on the change in prestroke health behaviors in Chinese patients with hypertensive stroke over a decade. OBJECTIVES: The aims of this study were to determine whether prestroke health behaviors of patients with hypertensive stroke changed over a decade and to explore the predictors of prestroke health behaviors over a decade. METHODS: This study used data from 2 cross-sectional studies conducted in the neurology departments of 3 hospitals in Guangzhou, China. In total, 110 hypertensive stroke patients were recruited in stage I (2008-2009), and 119 hypertensive stroke patients were recruited in stage II (2018-2019). Patients' stroke knowledge was measured by the Stroke Knowledge Questionnaire. Patients' prestroke health behavior was measured by the Health Behavior Scale for Stroke Patients. RESULTS: The total score of prestroke health behaviors significantly increased over the decade ( P < .001), but the scores of the subcategories of low-fat diet, low-sugar diet, and blood pressure checkups decreased over the decade ( P < .05). Stroke knowledge was a significant predictor of prestroke health behaviors in stage I ( P < .05). Besides stroke knowledge, sex and age were significant predictors of prestroke health behaviors in stage II ( P < .05). CONCLUSIONS: Prestroke health behaviors of hypertensive stroke patients significantly improved over the decade. Moreover, prestroke health behaviors were significantly influenced by stroke-related knowledge over the decade. Healthcare providers should focus in particular on assisting patients who are male, young, and middle-aged, and lack stroke-related knowledge to improve their prestroke health behaviors, especially in terms of adherence to a low-fat/low-sugar diet and regular blood pressure checks. Abstract : Supplemental digital content is available in the text.